Untangling RFID Privacy Models. (11th February 2013) - Coisel, Iwen; Martin, Tania
Abstract : The rise of wireless applications based on RFID has brought up major concerns on privacy. Indeed nowadays, when such an application is deployed, informed customers yearn for guarantees that their privacy will not be threatened. One formal way to perform this task is to assess the privacy level of the RFID application with a model. However, if the chosen model does not reflect the assumptions and requirements of the analyzed application, it may misevaluate its privacy level. Therefore, selecting the most appropriate model among all the existing ones is not an easy task. This paper investigates the eight most well-known RFID privacy models and thoroughly examines their advantages and drawbacks in three steps. Firstly, five RFID authentication protocols are analyzed with these models. This discloses a main worry: although these protocols intuitively ensure different privacy levels, no model is able to accurately distinguish them. Secondly, these models are grouped according to their features (e.g., tag corruption ability). This classification reveals the most appropriate candidate model(s) to be used for a privacy analysis when one of these features is especially required. Furthermore, it points out that none of the models are comprehensive. Hence, some combinations of features may not match any model. Finally, the privacy properties of the eight models are compared in order to provide an overall view of their relations. This part highlights that no model globally outclasses the other ones. Considering the required properties of an application, the thorough study provided in this paper aims to assist system designers to choose the best suited model.